The sun also rises - Erwin, Suzanne K (University of Cape Town, 2015)
This is an adaptation of 'Fiesta: The Sun Also Rises'. The story is changed in form and function from a book into a screenplay. And so, Hemingway's vivid source material is transposed from its origin as a literary work into a pictorial outline of a film. An adaptation of Ernest Hemingway's novel. A screenplay by Kate Erwin.